ANIMALS IN AN AGRICULTURAL LANDSCAPE? HUMAN-WILDLIFE CONFLICT IN NAMIBIA‟S COMMUNAL AREAS - Gargallo, E. (II International Meeting Histories of Nature and Environments. Shaping Landscapes, 2019)
Since the 1990s Namibia has been depicted as one of the most successful examples of conservation outside of officially Protected Areas. Its programme of Conservancies has attempted to combine wildlife and agricultural development on Communal Lands, with some apparent achievements. The increase in game numbers, however, has led to an increase in Human-Wildlife Conflict incidents, sparking a diversity of debates between conservation institutions, government agencies, private companies and local communities, and among each of these actors. Are game numbers really higher now than in ‘historical’ times? Are wildlife-related damages as severe as it is claimed? Which is the best way to compensate peasants and herders? Is conservation ‘paying’ for its costs? Most importantly: which is the place of wildlife in agricultural and pastoral areas? Deciding if Communal Lands are ‘natural’ or ‘agricultural’ landscapes is a contested issue and influences government policies and communities’ perceptions and actions. Through the analysis of some specific case-studies we will try to understand these debates, to provide a nuanced view of events on the ground and to explore the potentialities and difficulties of combining wildlife and agropastoral activities on the same lands. The Namibian case can also provide some clues about the evolution of conservation in rural Africa.